Pengaruh Promosi Penjualan dan Harga terhadap Loyalitas Pelanggan pada Usaha Angkringan Repeatfoods Tasikmalaya - Syamsul Anwar; Hartanto Halim; Eman Sulaiman (MAMEN: Jurnal Manajemen, 2024)
This research aims to find out: (1) the impact of Sales Promotion on Customer Loyalty on Repeatfoods Tasikmalaya's Retaining business. (2) the effect of Price on Customers Loyality on the Retailing of Repeatefoods tasikmalayan. This type of research uses quantitative methods. The population in this study is a customer of the Repeatfoods Register of Lake Malaya with a total of 2550 people. Sampling technique using purposive sampling with a number of samples of 97 people. Data collection technique uses questionnaires that have been tested for validity and reliability. The analysis technique used in testing hypotheses is the technique of double linear analysis. The results of the research showed that: (1) Sales Promotion had a significant and positive impact on Customer Loyalty on Repeatfoods Lakes Listing business of 52.7% with a sign value of 0,000<0,05, and the regression coefficient had a positive value of 0.754. (2) The price has a significant impact on customer loyalty on the Repeatefoods lakes listing enterprise of 38.3% and proved with the sign value 0.000<0,05 and regression factor has a value of (-0,263).